Neuromodulation in Children with Drug-Resistant Epilepsy - Ali, Irfan; Houck, Kimberly M.; Sully, Krystal (Journal of Pediatric Epilepsy, 2023)
The introduction of neuromodulation was a revolutionary advancement in the antiseizure armamentarium for refractory epilepsy. The basic principle of neuromodulation is to deliver an electrical stimulation to the desired neuronal site to modify the neuronal functions not only at the site of delivery but also at distant sites by complex neuronal processes like disrupting the neuronal circuitry and amplifying the functions of marginally functional neurons. The modality is considered open-loop when electrical stimulation is provided at a set time interval or closed-loop when delivered in response to an incipient seizure. Neuromodulation in individuals older than 18 years with epilepsy has proven efficacious and safe. The use of neuromodulation is extended off-label to pediatric patients with epilepsy and the results are promising. Vagus nerve stimulation (VNS), responsive neurostimulation (RNS), and deep brain stimulation (DBS) are Food and Drug Administration-approved therapeutic techniques. The VNS provides retrograde signaling to the central nervous system, whereas DBS and RNS are more target specific in the central nervous system. While DBS is open-loop and approved for stimulation of the anterior nucleus of the thalamus, the RNS is closed-loop and can stimulate any cortical or subcortical structure. We will review different modalities and their clinical efficacy in individuals with epilepsy, with a focus on pediatric patients.
Keywords: neuromodulation; VNS; RNS; DBS; drug-resistant epilepsy